Presence of bacteria capable of PCB biotransformation in stormwater bioretention cells. Issue 12 (3rd January 2022) - Cao, Siqi; Davis, Allen; Kjellerup, Birthe V
ABSTRACT: Core samples from bioretention cell media as well as surface stormwater sediment samples from seven urban areas were collected to assess the potential for biotransformation activity of polychlorinated biphenyls (PCBs). The presence of putative organohalide-respiring bacteria in these samples was studied. Based on extracted DNA, Dehalobacter, Dehalogenimonas and Dehalococcoides were detected. Other organohalide-respiring bacteria like Desulfitobacterium and Sulfurospirillum were not studied. Bacteria containing the genes encoding for biphenyl 2, 3-dioxygenase ( bph A) or 2, 3-dihydroxybiphenyl 1, 2-dioxygenase ( bph C) were detected in 29 of the 32 samples. These genes are key factors in PCB aerobic degradation. Transcribed bacterial genes from putative organohalide-respiring bacteria as well as genes encoding for bph A and bph C were obtained from the microbial community, thus showing the potential of organohalide respiration of PCBs and aerobic PCB degradation under both aerobic and anaerobic conditions in the surface samples collected at the bioretention site. Presence and concentrations of 209 PCB congeners in the bioretention media were also assessed. The total PCB concentration ranged from 38.4 ± 2.3 ng/g at the top layer of the inlet to 11.6 ± 1.2 ng/g at 20–30 cm at 3 m from the inlet. These results provide documentation that bacteria capable of PCB transformation, including both anaerobic dechlorination and aerobic degradation, were present and active in the bioretention. Abstract : Transformation of polychlorinated biphenyls (PCBs) was shown in stormwater sediment and bioretention media with presence of active aerobic and anaerobic PCB-degrading bacteria